Analysis of pregnancy outcomes and associated risk factors for tuberculosis recurrence during pregnancy in patients with prior tuberculosis undergoing IVF-ET - Hongwei Li; Mingxia Gao; Xianghua Dong; Lili Zhang; Yue Yuan; Xuehong Zhang (BMC Pregnancy and Childbirth)
Abstract Objective This study aimed to investigate the risk factors and pregnancy outcomes associated with recurrent tuberculosis (TB) during pregnancy among patients with a history of TB who underwent in vitro fertilization and embryo transfer (IVF-ET). Methods A retrospective case-control study was conducted at the Reproductive Center of Lanzhou University First Hospital, covering the period from January 2005 to September 2023. The study included infertile patients who had undergo IVF and had a documented history of TB. Patients who experienced recurrent TB during pregnancy were designated as the study group, while those who did not experience recurrence were assigned to the control group, matched at a 1:2 ratio. Both univariate and multivariate analyses were performed to identify risk factors associated with pregnancy outcomes. Results Pregnancy and neonatal outcomes were significantly worse among patients in the study group who experienced TB recurrence following IVF-ET. Among the 26 patients in the study group, only four achieved live births, with two neonatal deaths occurring within two months of delivery. Significant risk factors for TB recurrence identified included the GnRH agonist protocol, elevated estradiol and progesterone levels on the trigger day, and twin pregnancies (P < 0.05). Further multivariate analysis confirmed that high estradiol levels (≥ 5000 pg/ml) on the trigger day and twin pregnancies were independent predictors of TB recurrence. Conclusion Elevated estradiol levels (≥ 5000 pg/ml) on the day of human chorionic gonadotropin (hCG) trigger, as well as twin pregnancies, have been identified as independent risk factors for recurrent TB among pregnant patients with a history of TB who undergo embryo transfer. Given these findings, it is advisable for such patients to consider single embryo transfer and to utilize frozen embryo transfer cycles to mitigate the associated risks.